Mobile Learning Berbasis Android Sebagai Media Pembelajaran Bahasa Inggris Pada SDN 1 Banjar Manis - Anggara, Anggara; Mardiyanto, Mardiyanto (JELTec (Journal of Learning Technology), 2025)
In today's modern era, technological advancements have transformed traditional face-to-face learning into information technology-based education. Books and teachers, once the primary sources of learning, are now supplemented by internet-based resources, especially during the Covid-19 pandemic, which required online learning innovations. One such innovation is mobile learning, defined as the use of mobile devices in teaching and learning processes. This study aims to develop electronic teaching materials in the form of mobile learning for the English subject at SDN 1 Banjar Manis. English is a compulsory subject at the elementary level, emphasizing interaction and vocabulary development to support daily communication skills. The mobile learning application allows students to download teaching materials via smartphones installed with the mobile learning platform. The application was developed using Android Studio, Notepad, PHP, a MySQL database, and designed with Photoshop. With this application, teachers and students can easily interact online, and learning materials can be accessed anytime and anywhere, making the learning process more flexible and effective.